Diane - Clarke, Alan; Whitson, David; Hall, Peter; Duvitski, Janine; Mills, Frank; Preece, Tim (Alan Clarke at the BBC, Volume 1: Dissent, 2016)
Diane Weaver (played by Janine Duvitski) is a teenage girl living with her single father. She is an awkward girl with is picked on a bit by the local boys, though there is one particular boy who sees her through romantic eyes. Jim (played by Paul Copley) is nice to her, innocently asks her for kisses, but is a church youth who does not want to take things further because of his faith. He asks Diane to watch him play soccer with his team and also to go the church with him, but she is not keen on him as much as he is to her. Diane's father (played by Frank Mills) is a stern, angry, and bitter old man with a bad combover. He often yells at the boys in the area and he is very stern with his only daughter. Diane has a deep secret in which she doesn't know how to reveal or who to reveal to, but in turn would change many of the lives around her. [dvdcompare.net]